Lysozyme supplement enhances antioxidant capacity and regulates liver glucolipid metabolism in weaned piglets - Wu, Yuying; Zhang, Huihui; Zhang, Yonggang; Xie, Chunyan; Chen, Guoshun (Frontiers in Veterinary Science, 2025)
IntroductionLysozyme (LZ), a naturally occurring antimicrobial peptide, has demonstrated beneficial bioactivities. This study aimed to investigate the effects of dietary LZ supplementation on hepatic antioxidant function and glucolipid metabolism in weaned piglets.MethodsForty-eight weaned piglets (Landrace × Yorkshire, 22 days old) were randomly assigned to two dietary treatments: a control (CON) group fed a basal diet, and an LZ group fed the basal diet supplemented with 0.1% LZ for 19 days. Liver index and serum biochemical parameters were measured. Hepatic antioxidant enzyme activities and the mRNA expression of genes related to antioxidant function, lipid metabolism, and gluconeogenesis were determined. Liver fatty acid profiles were also analyzed.ResultsDietary LZ supplementation significantly increased the liver index and serum concentrations of triglyceride (TG), total cholesterol (TC), and Low-Density Lipoprotein Cholesterol (LDLC) (p < 0.05). In the liver, LZ significantly enhanced catalase (CAT) activity and up-regulated the mRNA expression of antioxidant genes, including NQO1, Nrf2, MnSOD, and CAT (p < 0.05). Furthermore, LZ altered the hepatic fatty acid profile by increasing the contents of C16:1, C17:0, C20:3n6, and C18:1n9t (p < 0.05). Gene expression analysis revealed that LZ up-regulated CPT1α and PPARα (p < 0.05) but down-regulated SCD and SREBP1 (p < 0.05). Additionally, LZ supplementation significantly increased the mRNA expression of gluconeogenic enzymes, including PEPCK, PC, and G6PC (p < 0.05).DiscussionThe results indicate that dietary LZ supplementation enhances the hepatic antioxidant defense system, likely through activation of the Nrf2 signaling pathway. Concurrently, LZ modulates lipid metabolism by promoting fatty acid oxidation (via up-regulation of PPARα and CPT1α) and inhibiting lipogenesis (via down-regulation of SREBP1 and SCD). The up-regulation of key gluconeogenic genes suggests improved hepatic glucose production. In conclusion, LZ improves antioxidant capacity and regulates glucolipid metabolism in the liver of weaned piglets, supporting its potential as a functional feed additive in pig production.